Herreria glaziovii (Agavoideae, Asparagaceae)—typification and a new synonym - Lopes, Rosana Conrado; Andreata, Regina Helena Potsch (Phytotaxa, 2012)
This paper provides a new circumscription, typification, and synonym of Herreria glaziovii. It also presents a full description, with illustrations and a distribution map, and with new records and pertinent comments.